A phase-field model for shock-induced α-γ phase transition of RDX. (January 2017) - Rahul; De, Suvranu
Abstract: A thermodynamically consistent continuum phase-field model has been developed to investigate the role of shock-induced solid-solid phase transformation in the deformation mechanisms of molecular single crystals. The effects of microstructural evolution and phase transformation are distinguished and modeled within a crystal plasticity framework that is developed for single crystals at high strain rate. When applied to 1, 3, 5-trinitroperhydro-1, 3, 5-triazine (RDX) single crystal, the model predicts α-γ phase transition within the experimentally observed range of shock stresses. Phase-field simulations suggest that the α-γ phase transition requires finite time to occur, where plasticity tends to delay the transition. Phase transformation is associated with stress relaxation, and increased temperature rise and associated shock-sensitivity. The shock response of α-γ phase transition is orientation dependent. Highlights: Phase-field model for shock-induced solid-solid phase transformation. Microstructural evolution and phase transition modeled within crystal plasticity. Model predicts α-γ phase transformation of RDX within range of shock stresses. α-γ transition requires finite time to occur and associated with temperature rise. Shock response of α-γ phase transition of RDX is orientation dependent.